The Use of ‘Know What Learned’ Strategy (KWL) to Improve Student’s Reading Comprehension at the Second Grade of SMA Negeri 14 Maluku Barat Daya - Laumaly, Alika; Binnendyk, Sophia; Meyer, Fredi (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2022)
The research explores how the Know What Learned (KWL) strategy improves students' reading comprehension in the second grade of SMA Negeri 14 MBD. It also examines the students' responses to implementing the Know What Learned strategy in reading comprehension in the Second Grade of SMA Negeri 14 MBD. The research method was Classroom Action Research (CAR), which consisted of two cycles. The data was collected through tests, questionnaires, and observation checklists as instruments. The result of the first (1) cycle showed that all students played actively in class, but students' participation was only 65%, and students experienced an increase in cycle two (2) of 100%. Based on the explanation above, the Know What Learned strategy improved students' reading comprehension in the Second grade of SMA Negeri 14 MBD.